The study of mosque architecture in Sarawak under the leadership of Pehin Sri Haji Abdul Taib Mahmud / Jamil Haji Hamali... [et al.] - Haji Hamali, Jamil; Wan Hassan, Sharifah Zakiah; Jimel, Clemet; Karim, Abdul Khalid; Mohd Muslim Tan, Ellyana; Muhammad Azmi, Safrina (2012)
This research aims at identifying mosques with distinctive design concepts and architecture in Sarawak built or reconstructed under the leadership of the Chief Minister Pehin Sri Haji Abdul Taib Mahmud and then reproducing these mosques in pictorial representations for the purpose of documentation and recording. The information and documentations gathered will then be compiled in a database system for future use. Producing a database on mosques in Sarawak is significant in the context of UiTM Sarawak as The Borneo Islamic Research and Propagation Centre, the base for research work and experiences on Islamic propagation in Borneo. It is a known fact that the aesthetic and architectural values and roles of mosques in Peninsular Malaysia have been well documented. However, there is a dearth in attempts to capture and study the design concepts and architectural forms as well as the roles of mosques in Sarawak, and as such this study is proposed. Only mosques that have distinctive design concepts and architecture will be studied. A random survey on the possible locations of the mosques in Sarawak which have aesthetic designs and architectural concepts will be conducted, guided by the book on the profile of the mosques in Sarawak (2009) produced by the Majlis Islam Sarawak. Photographic study will be carried out to establish the different design concepts and architectural elements of the selected mosques in Kuching, Samarahan/Asajaya, Serian, Lundu, Sri Aman Sibu, Mukah, Bintulu, Belaga, Miri, Bario, Lawas, Bakelalan, Long Semdoh, Limbang, Marudi, Long Bedian and Mulu. The study is significant in that the published work, particularly, the pictorial documentation that will be produced will be able to provide the views and evidence of mosques in Sarawak which have distinctive design concepts and architectural elements.